Pearl Harbor Attack. hearings before the United States Joint Committee on the Investigation of the Pearl Harbor Attack, Seventy-Ninth Congress, second session. (U.S. Congressional Hearings., 1946)
Hearing includes numerous unnumbered charts, maps, photographs, and other exhibits of the Roberts Commission. Includes index to exhibits' illustrations, p. 2171-2173.